Participants in the Elderly Empowerment Program Posyandu Ngudi Utomo: Study in Indonesia - Malik, Abdul; Widhanarto, Ghanis Putra; Vitriani, Adhe Mella (Universitas Negeri Semarang, 2020)
Creating healthy, independent, quality and productive older adults can be performed through routine health care efforts, namely the need to pay attention to risk factors to improve the health of the elderly. This study aims to explain the process of empowering the elderly, explain the supporting and inhibiting factors in the process of allowing the elderly, and explain the outcomes of the elderly empowerment program through the posyandu. This qualitative study uses the subject of Posyandu management, posyandu’s cadres for elderly and elderly families. Data analysis is shown in an interactive model by describing complete description data. The results showed that the process of empowering the elderly starts from preparation, assessment, planning alternative programs, formulating action plans, implementation and evaluation; while supporting factors are enthusiastic elderly who are high enough to know the health and support of the elderly family. Awareness is still low even there is a lack of infrastructure. The implication of this research for the field of community empowerment studies is to provide the benefits of preliminary studies for the development of betterquality empowerment models.